DYNAMIC ANALYSIS OF LAMINA TED COMPOSITE MAGNETO-THERMO-ELECTRO-ELASTIC SHELL - Albarody, Thar M. Sadri (2012)
Modeling of a piezo-laminated shell structure and/or shell embedded in a smart material lamina that is influenced by a magneto-thermo-electro-elastic load represent a challenge to be formulated and solved. In the present work, the fundamental theory was derived based on the generic first-order transversely shearable deformation theory and involved the Codazzi-Gauss geometrical discretion, low-and high-frequency motions, and thin, moderately thick, and/or thick effect. In which the present invented equations and their desired boundary conditions were strenuously derived using Hamilton's principle with the cooperation of Gibbs free energy functions. The theory was cast in a version of a general laminated composite shell of revolution, in order to be simplified to account for most of the occurring shell geometries, and intended for a wide range of common smart materials. Furthermore, a vibrational model for the piezo-laminated shell structure when subjected to fully interactive actions among mechanical, electric, magnetic, and thermal forces was provided efficaciously. Whereupon, sensor outputs and/or actuator input of the piezoelectric and/or magnetostrictive layer due to the direct and/or converse piezoelectric, piezomagnetic, electromagnetic, pyromagnetic and pyroelectric effects, as well as the effect of thermalloading were established arithmetically. A laminated composite shell of zero and larger curvature, having a rectangular plane-form and containing a smart material lamina was selected to assess the internal evenness of the presented model. The generic forced solution procedure for the response was the candidate to formulate the problem exactly in simply supported boundary conditions. The frequencies, center deflection, in-plane and inter-laminar stresses, electric and magnetic amplitudes, electrical displacement, and magnetic induction were evaluated for all the estimated matters.